Interferon-stimulated genes—essential antiviral effectors implicated in resistance to Theiler's virus-induced demyelinating disease. Issue 1 (December 2015) - Li, Lin; Ulrich, Reiner; Baumgärtner, Wolfgang; Gerhauser, Ingo
Abstract Background Experimental infection of mice with Theiler's murine encephalomyelitis virus (TMEV) is used as an animal model of human multiple sclerosis. TMEV persists in susceptible mouse strains and causes a biphasic disease consisting of acute polioencephalomyelitis and chronic demyelinating leukomyelitis. In contrast, resistant mice eliminate the virus within 2 to 4 weeks, which seems to be based on a strong antiviral innate immune response including the activation of the type I interferon (IFN) pathway. Several interferon-stimulated genes (ISGs) such as IFN-stimulated protein of 15 kDa (ISG15), protein kinase R (PKR), and 2′5′-oligoadenylate synthetase (OAS) function as antiviral effectors and might contribute to virus elimination. Nevertheless, detailed investigations of the type I IFN pathway during TMEV-induced demyelinating disease (TMEV-IDD) are lacking. Methods The present study evaluated microarray data of the spinal cord obtained from susceptible SJL/J mice after TMEV infection focusing on IFN-related genes. Moreover, ISG gene and protein expression was determined in mock- and TMEV-infected SJL/J mice and compared to its expression in resistant C57BL/6 mice using real- time PCR, immunohistochemistry, and immunofluorescence. Results Interestingly, despite of increased ISG gene expression during TMEV-IDD, ISG protein expression was impaired in SJL/J mice and mainly restricted to demyelinated lesions. In contrast, high ISG protein levels were found in spinal cord gray and white matter of C57BL/6 compared to SJL/J mice in the acute and chronic phase of TMEV-IDD. In both mouse strains, ISG15 was mainly found in astrocytes and endothelial cells, whereas PKR was predominantly expressed by microglia/macrophages, oligodendrocytes, and neurons. Only few cells were immunopositive for OAS proteins. Conclusions High levels of antiviral ISG15 and PKR proteins in the spinal cord of C57BL/6 mice might block virus replication and play an important role in the resistance to TMEV-IDD.